The Foundations of Mozart Scholarship - Irvine, Thomas (Current Musicology, 2006)
What are the foundations of Mozart scholarship? The “facts” -there are many of them, and we are always learning more-of a remarkable composer’s short life? Or the meanings we read in that life, and the meanings we experience in the music Mozart left behind? The composer’s present jubilee year offers a chance to reflect on these questions. My reflections begin with a polemical call for change in Mozart scholarship proposed more than forty years ago by a young music historian to the skeptical audience of around-table discussion at an international conference. The young scholar, Wolfgang Plath, had just assumed the editorship of the largest Mozart project of his day (and of ours), the Neue Mozart-Ausgabe. The tone of his argument interests me as well as its contents: it was a polemic, designed as much to discredit the position of his opponents as to strengthen his own position. Plath’s “straw man” was the school of German historiography that dominated writing in history and the history of the arts for more than a century, a school that sought, above all else, to discern meaning in history’s ebb and flow. His critique, as we shall see, was as controversial as it was effective; I will argue here that specialist Mozart scholarship today has been shaped in no small part by it. Indeed, the issues Plath raised in making his argument have implications that extend far beyond the narrow confines of Mozart studies.